From social responsibility to flourishing, the path towards business sustainability - Ayoub Derdabi; Ondřej Dvouletý (Ekonomický Časopis)
Sustainability in business is a construct that has received much attention from scholars in the last few years. The inclusion of sustainability in a company's strategy and operations is becoming almost imperative due to various internal and external pressures. Much less, however, is known about the pathways of companies and the implementation of sustainable principles into their daily business. The study is based on the review of existing concepts and models. This paper offers a conceptual pathway model that extends the existing models for different stages with a gradual environmental impact and profitability that companies can follow. Notably, it has been argued that sustainability can have both a social and environmental impact and a positive impact on companies' competitiveness and profitability. However, developing and integrating sustainable practices in a company can be challenging, and its implementation is risky. Sustainability is also not a leap, but it must be done gradually. Companies must plan their sustainability strategy properly, engage the stakeholders, assess and monitor their impact and develop transparent communication. The article notes the social interactions needed to advance and achieve sustainable business supply chains. The added value of the study is a five-stage gradual model, helping companies to realise the important steps towards making their business more sustainable.